Users' perceptions on Infolib Library and Information Systems - Laroza, Gerry O. (2007)
The main concern of this study was to assess the Infolib Library and Information Systems (Infolib) modules and their degree of completeness and usefulness as part of the computerization of the library services and how these features might be improved in the future. The main instrument that was used in the research is a survey questionnaire posted on the Web. This method helped the researcher to have efficient and effective data collection system. Librarians play a vital role in the computerization of library services, thus, more than seventy (70) percent of the respondents clearly indicated that, to a large extent, Infolib satisfies the users in the computerization of some of the library services such as storing, editing and retrieval of bibliographic information, borrowing and returning of materials and report generation. However, the study also showed that there is a need to improve the quality of Infolib in order to meet or exceed the user's demands and requirements. The user's opinions are valuable in checking the expected champions, error detection and improvement of the software quality as well. The areas where improvements were recommended are in cataloging, periodical articles, circulation, OPAC, maintenance and reports.